The 2005 survey of information systems research in Australia - Pervan, Graham; Shanks, G. (Dept. of Business Systems, University of Wollongong & School of Computing and Information Technology, Monash University, 2003, 2006)
As part of a study to investigate the state of Information Systems research in Australia, a survey of the heads of all IS discipline groups in Australian universities was conducted in mid 2005. The study revealed a wide range of topics researched (with rapid growth in Electronic Commerce and Knowledge Management), a range of foci, a balance between positivist and interpretivist research, survey was the most frequently used research method, and most research was directed at informing IS professionals. A SWOT analysis identified the growing importance of industry relevance and collaboration.